2002
DOI: 10.2134/jeq2002.2410
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 14C‐Atrazine Bound Residues in Brown Soil and Rendzina Fractions

Abstract: The remobilization and the fate of 14C-ring labeled atrazine (6-chloro-N2-ethyl-N4-isopropyl-1,3,5-triazine-2,4-diamine) bound residues was examined in relation with the turnover of natural soil organic matter. Soil fractions of a brown soil and a rendzina were incubated under controled laboratory conditions. The mineralization of natural organic matter and atrazine-bound residues was respectively estimated by the amounts of CO2 and 14CO2 evolved during the incubation. The remobilization and distribution of 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Treatment T4, in which the soil did not go through the process of sterilization, presented the lowest mean value for extractable residues, indicating that a biological degradation of atrazine occurred. This result corroborates with MUNIER-LAMY et al (2002), who also observed that the presence of the natural soil microbiota led to a decrease in the amount of extractable residues of atrazine after 120 days of incubation. The means followed by the same letter in the column do not differ among themselves at 5% significance by the Scott-Knott Test.…”
Section: Resultssupporting
confidence: 91%
“…Treatment T4, in which the soil did not go through the process of sterilization, presented the lowest mean value for extractable residues, indicating that a biological degradation of atrazine occurred. This result corroborates with MUNIER-LAMY et al (2002), who also observed that the presence of the natural soil microbiota led to a decrease in the amount of extractable residues of atrazine after 120 days of incubation. The means followed by the same letter in the column do not differ among themselves at 5% significance by the Scott-Knott Test.…”
Section: Resultssupporting
confidence: 91%
“…DIA and DEA are more toxic than atrazine, while HA is less mobile than atrazine (Munier-Lamy, Feuvier, and Chone 2002). The degradation of atrazine to HA proceeds chemical transformations at low pH in the presence of humic acids.…”
Section: Introductionmentioning
confidence: 99%